PENINGKATAN KOMPETESI MELALUI SELF-CONCEPT PARA PENGRAJIN TAHU TEMPE PRIMKOPTI SWAKERTA, SEMANAN JAKARTA BARAT - Aseanty, Deasy; Indriyarti, Eko Retno; Puspa, Tiara; Tanuwijaya, Justine; Kesumo, Nurhastuty; Setiawan, Audita; Gunarto, Gunarto (Universitas Bunda Mulia, 2021)
The decline in the turnover of tofu and tempe craftsmen in the Semanan area, Kali Deres sub-district, West Jakarta, has caused the tofu and tempeh craftsmen to have to think of strategies to keep their production running and increase sales. In addition, craftsmen are forced to reduce the amount of production compared to usual to prevent oversupply due to a decrease in demand. In addition, the price of the tofu and tempe was also increased from usual to cover the losses received. Among the various factors that can cause it, one important factor is increasing the competence of craftsmen through self-concept. This aspect concerns the positive values and attitudes of tofu and tempeh craftsmen related to the business. The community service carried out aims to increase competence through self-concept in the tofu and tempeh craftsman group in this region. The community service method is carried out using online counseling by providing material and question and answer (Q&A) discussions. The service was carried out smoothly. The measurement of the effectiveness of this abdimas uses a simple descriptive-quantitative by explaining the increase in insight into the competence of the craftsmen in terms of self-concept. In addition, the results of the service carried out were able to provide increased insight into tofu and tempe craftsmen in this region regarding self-concept-based competencies. The most significant improvement was found on a fairly good achievement scale (from 0% to 48%) where 5-6 items were answered correctly by the participants. The importance of the ability to manage creative marketing and sales strategies by utilizing online (digital) media is a recommendation for the next abdimas topic.